How Toll-like receptors influence Parkinson’s disease in the microbiome–gut–brain axis - Zhang, Ziyi; Liu, Zhihui; Lv, Ao; Fan, Chenhui (Frontiers in Immunology, 2023)
Recently, a large number of experimenters have found that the pathogenesis of Parkinson’s disease may be related to the gut microbiome and proposed the microbiome–gut–brain axis. Studies have shown that Toll-like receptors, especially Toll-like receptor 2 (TLR2) and Toll-like receptor 4 (TLR4), are key mediators of gut homeostasis. In addition to their established role in innate immunity throughout the body, research is increasingly showing that the Toll-like receptor 2 and Toll-like receptor 4 signaling pathways shape the development and function of the gut and enteric nervous system. Notably, Toll-like receptor 2 and Toll-like receptor 4 are dysregulated in Parkinson’s disease patients and may therefore be identified as the core of early gut dysfunction in Parkinson’s disease. To better understand the contribution of Toll-like receptor 2 and Toll-like receptor 4 dysfunction in the gut to early α-synuclein aggregation, we discussed the structural function of Toll-like receptor 2 and Toll-like receptor 4 and signal transduction of Toll-like receptor 2 and Toll-like receptor 4 in Parkinson’s disease by reviewing clinical, animal models, and in vitro studies. We also present a conceptual model of the pathogenesis of Parkinson’s disease, in which microbial dysbiosis alters the gut barrier as well as the Toll-like receptor 2 and Toll-like receptor 4 signaling pathways, ultimately leading to a positive feedback loop for chronic gut dysfunction, promoting α-synuclein aggregation in the gut and vagus nerve.